Oxidized CaMKII (Ca2+/Calmodulin-Dependent Protein Kinase II) Is Essential for Ventricular Arrhythmia in a Mouse Model of Duchenne Muscular Dystrophy. (April 2018) - Wang, Qiongling; Quick, Ann P.; Cao, Shuyi; Reynolds, Julia; Chiang, David Y.; Beavers, David; Li, Na; Wang, Guoliang; Rodney, George G.; Anderson, Mark E.; Wehrens, Xander H.T.
Abstract : Background: Duchenne muscular dystrophy patients are prone to ventricular arrhythmias, which may be caused by abnormal calcium (Ca 2+ ) homeostasis and elevated reactive oxygen species. CaMKII (Ca 2+ /calmodulin-dependent protein kinase II) is vital for normal Ca 2+ homeostasis, but excessive CaMKII activity contributes to abnormal Ca 2+ homeostasis and arrhythmias in cardiomyocytes. Reactive oxygen species induce CaMKII to become autonomously active. We hypothesized that genetic inhibition of CaMKII oxidation (ox-CaMKII) in a mouse model of Duchenne muscular dystrophy can alleviate abnormal Ca 2+ homeostasis, thus, preventing ventricular arrhythmia. The objective of this study was to test if selective loss of ox-CaMKII affects ventricular arrhythmias in the mdx mouse model of Duchenne muscular dystrophy. Methods and Results: 5-(6)-Chloromethyl-2, 7-dichlorodihydrofluorescein diacetate staining revealed increased reactive oxygen species production in ventricular myocytes isolated from mdx mice, which coincides with elevated ventricular ox-CaMKII demonstrated by Western blotting. Genetic inhibition of ox-CaMKII by knockin replacement of the regulatory domain methionines with valines (MM-VV [CaMKII M281/282V]) prevented ventricular tachycardia in mdx mice. Confocal calcium imaging of ventricular myocytes isolated from mdx :MM-VV mice revealed normalization of intracellular Ca 2+ release events compared with cardiomyocytes from mdx mice. Abnormal action potentials assessed by optical mapping in mdx mice were also alleviated by genetic inhibition of ox-CaMKII. Knockout of the NADPH oxidase regulatory subunit p47 phox normalized elevated ox-CaMKII, repaired intracellular Ca 2+ homeostasis, and rescued inducible ventricular arrhythmias in mdx mice. Conclusions: Inhibition of reactive oxygen species or ox-CaMKII protects against proarrhythmic intracellular Ca 2+ handling and prevents ventricular arrhythmia in a mouse model of Duchenne muscular dystrophy. Abstract : Supplemental Digital Content is available in the text.